Structural Differences between Pri-miRNA Paralogs Promote Alternative Drosha Cleavage and Expand Target Repertoires - Xavier Bofill-De Ros; Wojciech K. Kasprzak; Yuba Bhandari; Lixin Fan; Quinn Cavanaugh; Minjie Jiang; Lisheng Dai; Acong Yang; Tie-Juan Shao; Bruce A. Shapiro; Yun-Xing Wang; Shuo Gu (Cell Reports, 2019)
Summary: MicroRNA (miRNA) processing begins with Drosha cleavage, the fidelity of which is critical for downstream processing and mature miRNA target specificity. To understand how pri-miRNA sequence and structure influence Drosha cleavage, we studied the maturation of three pri-miR-9 paralogs, which encode the same mature miRNA but differ in the surrounding scaffold. We show that pri-miR-9-1 has a unique Drosha cleavage profile due to its distorted and flexible stem structure. Cleavage of pri-miR-9-1, but not pri-miR-9-2 or pri-miR-9-3, generates an alternative miR-9 with a shifted seed sequence that expands the scope of its target RNAs. Analyses of low-grade glioma patient samples indicate that the alternative-miR-9 has a potential role in tumor progression. Furthermore, we provide evidence that distortion of pri-miRNA stems induced by asymmetric internal loops correlates with Drosha cleavage at non-canonical sites. Our studies reveal that pri-miRNA paralogs can have distinct functions via differential Drosha processing. : By studying the processing of pri-miR-9 family, Bofill-De Ros et al. demonstrate that the tertiary structure of pri-miRNA triggers alternative biogenesis. Drosha cleaves pri-miR-9-1 at an additional site because of its distorted and flexible lower stem, generating a 5′ isomiR that regulates a distinct set of genes in low-grade glioma. Keywords: primary miRNA, miR-9, isomiRs, Drosha, microprocessor, RNA structure, paralogs